2023
DOI: 10.5253/arde.2022.a29
|View full text |Cite
|
Sign up to set email alerts
|

The Fortunes of Migratory Birds from Eurasia: Being on a Tightrope in the Sahel

Abstract: Many studies have shown that rainfall in the Sahel has a great influence on population trends of European bird species that spend the northern winter there. African bird species living in the Sahel, notably those that forage on the ground, have also shown significant declines, but independent of rainfall. This paper summarises the results of field data gathered in the entire Sahel and evaluates the many factors that play a role in the fortunes of birds. (1) Rainfall determines the extent of open water in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 201 publications
0
3
0
Order By: Relevance
“…More recently, studies, including those based on data from electronically tagged birds, have suggested that it is the timing of departure from Africa [56][57][58] or on migration [5,59] that determines the variability in the spring arrival of species such as those reported in the current paper. More research on the entire migration cycle of these birds is needed [60,61], and work on the consequences of asynchronous change (e.g., [62]) is gaining pace.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies, including those based on data from electronically tagged birds, have suggested that it is the timing of departure from Africa [56][57][58] or on migration [5,59] that determines the variability in the spring arrival of species such as those reported in the current paper. More research on the entire migration cycle of these birds is needed [60,61], and work on the consequences of asynchronous change (e.g., [62]) is gaining pace.…”
Section: Discussionmentioning
confidence: 99%
“…To conserve this species, it is essential to identify roost sites and their associated foraging areas, taking into account potential threats such as land use changes, or the use of pesticides for controlling outbreaks of potential prey species (Mullie 2021). Indeed, Sahel landscapes are anticipated to undergo substantial and rapid transformations in the coming decades due to development and climatic changes (Thiollay 2007, Zwarts et al 2023c.…”
Section: Conservation Implicationmentioning
confidence: 99%
“…vegetation (Moreau 1972, Zwarts et al 2023. Within the Sahel this dry season typically extends beyond the onset of spring migration, whereas a few hundred kilometres towards the south (in the Sudanian and Guinean regions) most migrants depart after the first rainfall, and consequently experience regrowth and foliation of the vegetation at the end of the nonbreeding season (Zwarts et al 2023).…”
mentioning
confidence: 99%